Implications of Planning and Management for the Development of Sustainable Cultural Heritage Tourism in Malaysia - Aisyah, Siti (Advances in Tourism Studies, 2023)
This study investigates the development of cultural heritage tourism in Malaysia and its sustainability. It highlights the importance of meeting local community needs, satisfying tourist demands, and safeguarding natural and cultural resources for sustainable tourism development. The study employs questionnaires, surveys, and interviews to explore management issues and government involvement. Findings reveal shortcomings in definitions, management issues, and limited community involvement. The study calls for improved tourist services, promotion of diverse cultural elements, and proposes a Sustainable Cultural Heritage Tourism Framework. It contributes new knowledge and can guide future policy actions.